Can Small Hepatocellular Carcinoma be Cured by Percutaneous Acetic Acid Injection Therapy? - Fan, S.-T. (Hindawi Publishing Corporation, 1997)
To assess the efficacy of ultrasound (US)-guided percutaneous acetic acid (in concentrations of 15%, 20%, 30%, 40%, and 50%) injection for small hepatocellular carcinomas (HCCs) for long-term prognosis, percutaneous acetic acid injection using 15% to 50% acetic acid was performed in 91 patients with one to four HCCs smaller than 3 cm during the past 6.5 years. During the series of treatment sessions for each patient, the same concentration of acetic acid was used. All tumors could be treated successfully with percutaneous acetic acid injection despite the differences in acetic acid concentration used. The number of treatment sessions to treat similar size of tumor was less when the higher concentration of acetic acid was used. No serious complications occurred as a direct sequela to percutaneous acetic acid injection. None of the tumor treated regrew. The 1-, 2-, 3-, 4-, and 5-year survival rates for 91 patients were 95%, 87%, 80%, 63%, and 49%, respectively. The 1-, 2-, 3-, 4-, and 5-year cancer-free survival rates of these patients were 83%, 54%, 50%, 37%, and 29%, respectively. Both liver function and size of tumor affected both survival rate and cancer-free survival rate significantly, but the number of tumors did not. The concentration of acetic acid did not affect the survival rate. Percutaneous acetic acid using 15% to 50% acetic acid will be effective therapy for small HCCs for long-term prognosis.